1990
DOI: 10.1111/j.1476-5381.1990.tb15801.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular responses to capsaicin in vitro and in situ

Abstract: 1 The cerebrovascular effects of capsaicin have been examined in vitro, in feline isolated cerebral arteries (circular segments, 2-3mm long, 300-400pum extended diameter) and, in situ, in pial arterioles (diameter 40-200jum) on the cortical surface of chloralose-anaesthetized cats.2 In isolated middle cerebral arteries, low concentrations of capsaicin (10 1-10-1OM) effected a concentration-dependent relaxation of vessels precontracted with prostaglandin F2l. This relaxant response was markedly attenuated by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 39 publications
3
43
1
Order By: Relevance
“…Another reason was that stimulation of sensory neuronal TRPV1 in the perivascular nerves evokes vasodilatation (Zygmunt et al, 1999), probably obscuring the vasoconstrictor response in many cases. In accordance with this latter mechanism, earlier reports showed concentration-dependent biphasic effects of TRPV1 stimulation; low dose capsaicin evoked dilatation, while higher concentrations resulted in constriction (Edvinsson et al, 1990;Dux et al, 2003). This suggested the involvement of different receptors or different pharmacology for TRPV1-mediating vascular dilatation and constriction.…”
Section: Pharmacology Of Trpv1 In Peripheral Arteriessupporting
confidence: 56%
See 1 more Smart Citation
“…Another reason was that stimulation of sensory neuronal TRPV1 in the perivascular nerves evokes vasodilatation (Zygmunt et al, 1999), probably obscuring the vasoconstrictor response in many cases. In accordance with this latter mechanism, earlier reports showed concentration-dependent biphasic effects of TRPV1 stimulation; low dose capsaicin evoked dilatation, while higher concentrations resulted in constriction (Edvinsson et al, 1990;Dux et al, 2003). This suggested the involvement of different receptors or different pharmacology for TRPV1-mediating vascular dilatation and constriction.…”
Section: Pharmacology Of Trpv1 In Peripheral Arteriessupporting
confidence: 56%
“…Vasoconstriction in response to TRPV1 stimulation was reported decades ago (Molnar and Gyorgy, 1967;Toda et al, 1972;Donnerer and Lembeck, 1982;Duckles, 1986;Edvinsson et al, 1990) and this effect was confirmed later (Szolcsanyi et al, 2001;Dux et al, 2003;Scotland et al, 2004;Keeble and Brain, 2006;Lizanecz et al, 2006). Nonetheless, these responses were not thought to be of interest.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, it seems likely that activation of cardiac C fiber by capsaicin may relax coronary artery by releasing CGRP. In our present studies, pretreatment with a high concentration of capsaicin, which causes a chemical desensitization of sensory nerves and renders them insensitive to further exposure to capsaicin [4,24], did not change the relaxation responses to subsequently applied capsaicin. Furthermore, pretreatment with capsazepine or ruthenium red, both of which block the release of neuropeptides from sensory nerve [14,22], did not alter the relaxation response to capsaicin.…”
Section: Discussionmentioning
confidence: 67%
“…In addition to this neuropeptide-mediated effect, capsaicin has a diverse effect on smooth muscle contractility and ion channel activity, depending on the species and preparations. Capsaicin relaxes bronchial smooth muscle through activation of Ca 2+ -activated K + channels [5,24], or constricts cerebral arteries by increasing Ca 2+ influx [4]. The inhibitory effect of capsaicin on Ca 2+ and K + current in cultured aortic smooth muscle cells has also been reported [15].…”
mentioning
confidence: 98%
“…CGRP is the strongest vasodilator found to date, acting via a nonendothelial mechanism and using adenylate cyclase as second messenger. 23,38 Electrical field stimulation or capsaicin treatment 39,40 causes local vasodilatation and release of CGRP from the perivascular nerve fiber endings. These effects are attenuated by administration of a CGRP blocker acting postsynaptically 4 -6,41,42 or a triptan acting at presynaptic sites.…”
Section: Introductionmentioning
confidence: 99%